Studies of Gallium Nitride (GaN) based High Electron Mobility Transistors (HEMTs) - Ong, Zi Kai (Nanyang Technological University, 2020)
GaN-based devices are wide bandgap semiconductor materials that are poised to supersede Si-based devices in power electronics and high frequency applications. GaN-based HEMTs have emerged as a forefront choice among other materials due to its high breakdown electric field, saturation velocity and thermal conductivity. Polarisation effects in the barrier layer of GaN HEMT induces 2DEG at the top of underlying buffer layer. In this channel layer, this 2DEG is spatially separated from scattering effects and very thin, achieving good electron mobility and density. Currently, the best performing GaN-based HEMTs are fabricated on SiC and Sapphire. However, high cost limits their commercial viability. Hence, there is an increasing interest in GaN-based HEMT on Si substrate, GaN-on-Si HEMT. In this project, not only is GaN grown on Si substrate, non-gold ohmic contacts are adopted into the structure to enable compatibility (no gold contamination) with Si-based processes used in foundries all over the world. In addition, even more cost saving will also be achieved. Last but not least, a thin lnAlN barrier is used instead of the usual AlGaN barrier due to advantages such as lower lattice mismatch with GaN. DC and RF characterization were conducted on GaN-on-Si HEMTs fabricated in this project. Si substrate is used for all fabricated HEMTs with Ti/Al gate contacts and Ta/Al ohmic contacts. The device with gate length (Lg) = 90nm, source-to-drain spacing (Lsd) = 1030nm and gate width (Wg) =2x20μm exhibited a maximum drain current Idmax of 1.721mA/mm. Peak transconductance was achieved at 473.432 mS/mm. Contact resistance Rc= 0.290 Ω.mm was recorded. The device with Lg = 80nm and Lsd = 750nm attained a cut-off frequency, fT, of 202 Ghz and a maximum oscillating frequency, fmax, of 93 Ghz.